2019
DOI: 10.1186/s12967-019-1828-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of CEA, CYFRA21-1 and NSE in monitoring tumor response to Nivolumab in advanced non-small cell lung cancer (NSCLC) patients

Abstract: Background CEA, CYFRA21-1 and NSE are tumor markers used for monitoring the response to chemotherapy in advanced adenocarcinoma, squamous cell carcinoma and small-cell lung cancer, respectively. Their role in cancer immunotherapy needs to be elucidated. Methods Patients with advanced non-small cell lung cancer (NSCLC) were treated with nivolumab 3 mg/kg every 2 weeks within the Italian Nivolumab Expanded Access Program. Blood samples were collected at baseline, at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 39 publications
(43 reference statements)
7
128
0
2
Order By: Relevance
“…However, except for PD-L1 tissue expression (>50%) that is used to select advanced NSCLC patients to receive pembrolizumab in the first line setting, no reliable prognostic or predictive marker is presently acknowledged for other ICIs. In this context, in preclinical studies, we found that circulating markers may have significant results [29,95,96]. Moreover, the correlation between PD-L1 expression on CTCs and prognosis of advanced patient cohorts treated with immunotherapy has been explored.…”
Section: Discussionmentioning
confidence: 98%
“…However, except for PD-L1 tissue expression (>50%) that is used to select advanced NSCLC patients to receive pembrolizumab in the first line setting, no reliable prognostic or predictive marker is presently acknowledged for other ICIs. In this context, in preclinical studies, we found that circulating markers may have significant results [29,95,96]. Moreover, the correlation between PD-L1 expression on CTCs and prognosis of advanced patient cohorts treated with immunotherapy has been explored.…”
Section: Discussionmentioning
confidence: 98%
“…To date, the role of PD-L1 expression as biomarker in immunotherapy is still controversial [11,29,30], and the identification of reliable indicators that might assess prognosis and efficacy of immunotherapy is being strongly pursued [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data at this time suggest that it may be reasonable to rechallenge patients with immunotherapy upon recurrence [6, 33, 4144], or treat oligometastatic recurrences with surgery or radiation therapy, with lower threshold to initiate systemic therapy following multiple recurrences or in those with higher burden of disease [6]. Furthermore, increased use of liquid biopsies (such as circulating tumor DNA) [45, 46], tumor markers (such as CEA, CA125) [47, 48], and blood parameters (such as NLR) [46] as biomarkers of response or relapse in ICI-treated patients will further identify early responders, discern CRs from occult disease, and guide therapy in patients with early progression.…”
Section: Discussionmentioning
confidence: 99%